THE USE OF DICTIONARY TO UNDERSTAND SIMILAR WORDS IN ENGLISH - Najamuddin Najamuddin (Universitas Islam Negeri Mataram, 2019)
A knowledge of words, phrases, clauses is essential to good writting andspeaking, but it doesn’t mean neglect the other part of grammar. The correction ofwriting and speaking is to concentrate on what we are saying rather than on how weare saying it. The problems might raise once speakers find similar words in meaningbut cotextually different in use. The study aims to investigate the forms of words thathave more than one correct meaning but different in use. The data were collected bysorting some potential words that have the same meanings in the dictionary as acontent analysis.The words were investigated in the dictionary and provided theirmeanings in forms of tables.The words were analysed qualitatively by looking at themeaning prescribed in dictionary and compared how they are used in a sentence. Itis found that words serve different purposes in language. Some words seem to havefunction words that cue a reader or speaker to the structure of the sentence suchas are, that, a, to, or, the, of, and so forth. Function words make spoken languagemeaningful and written language coherent and readable. Other words might refer ascontent words that communicate meaning in text. Clearly, students must know bothkinds of words to understand what they read.